Temporary immersion systems in plant biotechnology. Issue 6 (21st August 2014) - Georgiev, Vasil; Schumann, Anika; Pavlov, Atanas; Bley, Thomas
<x xml:space="preserve">Abstract</x> Plant tissue and organ cultures in vitro usually face technological challenges. When submerged cultivation of plant cells in a controlled environment is desired, the characteristic growth morphology and physiology of differentiated organ cultures present a problem in process scale‐up. Temporary immersion systems (TIS) were developed several decades ago. These systems are providing the most natural environment for in vitro culture of plant shoots and seedlings. Over the past few years, TIS have been recognized as a perspective technology for plant micropropagation, production of plant‐derived secondary metabolites, expression of foreign proteins, and potential solutions in phytoremediation. Nowadays, several TIS, operating on similar or divergent technological principles, have been developed and successfully applied in the cultivation of various plant in vitro systems, including somatic embryos and transformed root cultures. In this article, the operational principle and technological design of the most popular TIS are reviewed. In addition, recent examples of the application of temporary immersion technology for in vitro cultivation of plant tissue and organ cultures at laboratory and pilot scales are discussed. Finally, future prospects and challenges to the industrial realization of that fast‐developing technique are outlined.